PSYCHOSOCIAL EXPLANATION AND TREATMENT FOR ADOLESCENCES WITH GENDER DYSPHORIA - Yulia Wardani (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
Background: Indonesia faces ongoing social, religious and legal challenges in responding gender dysphoria (distress resulting from sex incongruence). It associated with poor mental health, self‑harm, substance misuse and impaired social functioning. Purpose: This study aims to review recent evidence (2015–2025) on psychosocial explanations of gender dysphoria and to summarize current approaches to psychosocial and medical treatment. Methods: A qualitative narrative review was conducted using EBSCO, PubMed and Medline (2015–Jan 2025). Data were organized into themes on: (1) diagnostic concepts and epidemiology, (2) psychosocial and developmental correlates, and (3) treatment models and outcomes. Results: Gender dysphoria is not classified as a mental disorder in ICD‑11 but frequently co‑occurs with significant psychiatric symptoms and adverse childhood experiences. Evidence on psychosocial interventions suggests that structured psychological support (individual, family‑based, or group) is generally safe and may improve mental health. Updated clinical guidance converges on a multidisciplinary model with comprehensive psychosocial assessment, psycho-education, family involvement and support for coping with stigma, with careful exploration of gender identity over time. Conclusion: A multidisciplinary, exploratory and gender‑affirming care pathway for adolescents with gender dysphoria, centered on psychosocial assessment and support, active involvement of families, and, where indicated, staged medical interventions.